Student Expectations and Quality of Postgraduate Education: The Case for Public Universities in Uganda - Kaggwa, Victoria Tamale; Sekiwu, Denis; Naluwemba, Esther Frances (Advances in Social Sciences Research Journal, 2017)
In order to chant John Stuart Mill’s Utility Theory in Service Delivery, this study focuses on the quality of student support in Postgraduate Education at Makerere University’s College of Education and External Studies (CEES). Using 50 Masters’ and Doctoral Student respondents, the study investigated an alleged gap between students’ expectations and experiences of service quality in Postgraduate programs offered by the College. Four dimensions play a cardinal role in the measurement of student support service quality in postgraduate education, namely supervision support, infrastructure, administrative support, and academic facilitation. The 4-dimensions are student dissatisfiers necessitating interventions to improve quality. From the Step-Wise Regression computations, support supervision and administrative support are the most important determinants of quality postgraduate support. As recommendations, support supervision and administrative support must be targeted as drivers of quality student support at this level. The Utilitarian Theory, if well-integrated, provides moral bounds in which quality support systems could be optimally scaled up.